1997
DOI: 10.1111/j.1600-0463.1997.tb05602.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone, Skin and Wound Healing—experimental studies in the rat

Abstract: Cop y r i g h t0 A P M I S 199 7 &PMUS I S S N 0 9 0 3 -4 6 5 x I S B N 8 7-16-156 78-1 ACKNOWLEDGEMENTS This thesis is based on experimental works performed at the Department of Connective Tissue Biology, Institute of Anatomy, University of Aarhus, Denmark during my employment as a research fellow. It was a fascinating and most inspiring time and I wish to convey my heartiest thanks to all members of the staff at the institute.Some specific people, however must be mentioned here. Above all special thoughts go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 301 publications
(248 reference statements)
0
5
0
5
Order By: Relevance
“…htm. The purpose of wound healing is to restore tissue continuity and resistance to externally applied forces 62 . In animal models, the progress of healing can be assessed by measuring the development of the mechanical strength of the wound 62 .…”
Section: Analytical Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…htm. The purpose of wound healing is to restore tissue continuity and resistance to externally applied forces 62 . In animal models, the progress of healing can be assessed by measuring the development of the mechanical strength of the wound 62 .…”
Section: Analytical Measuresmentioning
confidence: 99%
“…The purpose of wound healing is to restore tissue continuity and resistance to externally applied forces 62 . In animal models, the progress of healing can be assessed by measuring the development of the mechanical strength of the wound 62 . In the majority of the studies reviewed, evaluation of the skin models was accomplished by testing both the tensile and breaking strength of the wounded area with a tensiometer.…”
Section: Analytical Measuresmentioning
confidence: 99%
“…There are number of studies of electrostimulation and ultrasound therapy being benefi cial on secondary wound healing (22)(23)(24)(25)(26)(27)(28). Hydrotherapy, hyperbaric oxygen therapy, lasers, negative pressure therapy and a number of growth factors are reported to be useful in multiple studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that GH therapy in burn patients resulted in improved wound healing, delayed separation of eschars, increase in haemoglobin, serum albumin, calcium, phosphorus and glomerular filtration rate, and also a reduction in weight loss, nitrogen production rate, catabolic index, duration of sepsis and hospital stay 9 . A review clearly demonstrated that GH has advantageous effects on intact skin and wound healing 30 . To further assess this drug's potential radiation injury‐preventive effects, we studied the protective effect of GH in rats by using this radiation‐induced skin injury model.…”
Section: Discussionmentioning
confidence: 99%
“…9 A review clearly demonstrated that GH has advantageous effects on intact skin and wound healing. 30 To further assess this drug's potential radiation injury-preventive effects, we studied the protective effect of GH in rats by using this radiation-induced skin injury model.…”
Section: Discussionmentioning
confidence: 99%